2012
DOI: 10.1100/2012/909524
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Early Allergic Sensitization in the Lithuanian Birth Cohort

Abstract: Cohort studies are of great importance in defining the mechanism responsible for the development of allergy-associated diseases, such as atopic dermatitis, allergic asthma, and allergic rhinoconjunctivitis. Although these disorders share genetic and environmental risk factors, it is still under debate whether they are linked or develop sequentially along an atopic pathway. The current study was aimed to determine the pattern of allergy sensitization in the Lithuanian birth cohort “Alergemol” (n = 1558) establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Around 19.2% of MACS children had egg sensitization at 12 months compared to 6% in the German Multicenter Allergy Study . Although sensitization to cow's milk is known as the most common food allergen during infancy , we found that egg white and peanut were the most common sensitized foods in infancy. Australia has one of the highest prevalences of reported allergic diseases .…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Around 19.2% of MACS children had egg sensitization at 12 months compared to 6% in the German Multicenter Allergy Study . Although sensitization to cow's milk is known as the most common food allergen during infancy , we found that egg white and peanut were the most common sensitized foods in infancy. Australia has one of the highest prevalences of reported allergic diseases .…”
Section: Discussioncontrasting
confidence: 50%
“…Although the natural history of food sensitization has been described in early childhood , only three studies have investigated this question into late adolescence . The Poole and Odense birth cohorts were restricted by small sample sizes (n = 100 and n = 276, respectively) and did not assess peanut sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the PRISMA flowchart for our study selection and screening. Seventy‐five papers (based on 56 primary studies) were included in the narrative synthesis , and 30 studies were included in the meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, wheat and milk-derived ingredients were found in the analysed products; however, it is not possible to correlate these findings due to the disparity of time between the two studies. Further investigations need to be carried out in order to analyse the relation between food ingredients in cosmetic products and the development of immunoglobulin E (IgE) and non-IgE-mediated food allergies in Lithuania 37.…”
mentioning
confidence: 99%